Investigations of phytochemical, analgesic, anti-inflammatory and antipyretic effects of Ixora pavetta Andrews leaf - Mondal, Sumanta; Raja, S; Prasad, PNVSS; Suresh, Padilam (Journal of Nepal Pharmaceutical Association, 2015)
Ixora pavetta Andrews, (var.: I. Parviflora Vahl.) is a small tree or evergreen shrub belongs to the family Rubiaceae, and is used for many ailments, especially for the treatment of to treat chronic wounds, urinary diseases, skin infection, pulmonary troubles, liver disorder, hair tonic, sedative, diuretic, diarrhoea, dysentery, leucorrhoea and veneral diseases. Preliminary phytochemical screening of ethanol exract of I. pavetta leaf showed the presence of alkaloids, flavonoids, tannins and saponin glycoside. In the analgesic activity, ethanol extract provoked a significant reduction of the number of writhes in acetic acid-induced writhing response, also significantly reduced the licking time in both phases of the formalin test and highest analgesia in hot-plate test (P < 0.01) compared to the control group. The anti-inflammatory effects were investigated employing the both carrageenan and arachidonic acid -induced hind-paw oedema in rats and results of the study revealed the extract to have significant (P < 0.05) anti-inflammatory effects at a dose of 400 and 600 mg/kg p.o., rats in both the models. The antipyretic activity was evaluated using Brewer’s yeast induced pyrexia in rats and the extract showed significant lowering of body temperature in rats at doses of 400 and 600 mg/kg p.o., and no promising results with 200 mg/kg dose level. These findings suggest that ethanol extract of I. pavetta leaves possess potent anti-inflammatory, analgesic and antipyretics effects. DOI: http://dx.doi.org/10.3126/jnpa.v27i1.12146 Journal of Nepal Pharmaceutical Association 2014 Vol.XXVII: 20-27